Monitoring the decomposition of wealth-related inequality in the use of regular antenatal care in Egypt (1995–2014) - Zeinab Khadr (BMC Public Health, 2020)
Abstract Background Between 1995 and 2014 Egypt successfully increased the use of regular antenatal care (URAC) among women from 30.4 to 82.9%. The same period saw a decrease in the wealth-based inequality in URAC. This paper investigates the changes in the main determinants contributing to the wealth-based inequality in URAC for the 2 years of 1995 and 2014, and the determinants that underlined the declines in this inequality. Methods The secondary analysis was based on data from the 1995 and 2014 rounds of the Egypt Demographic and Health Survey. Logistic regression was implemented to model URAC for the 2 years and inequality was measured using the concentration index. Decomposition of the concentration index and Blinder -Oaxaca decomposition were implemented to assess the contribution of the URAC determinants to its inequality and the changes between 1995 and 2014. Results Decomposition of inequalities in URAC in 1995 and 2014 showed that social determinants were the main contributors to these inequalities. More than 90% of the inequalities were explained by the living in rural Upper Egypt, women and their husbands secondary and higher education, the household standard of living, and birth order. These same determinants were responsible for more than 76% of the decline in the inequality in URAC between 1995 and 2014. Wide spread of poverty in rural Upper Egypt was found to contribute significantly to the inequality in URAC. Women and their husbands who have secondary or higher education maintained their high odds of URAC. Conclusion Since poverty in rural Upper Egypt, and inequality in education and parity are crucial social determinants of URAC inequality and its change overtime, new policies and interventions need to focus not only on the health system but on social initiatives with an equity lens to tackle the structural causes underlying these factors and their inequalities.